Financial Literacy and Financial Behavior: Predicting Financial Well-Being Among Study Abroad Students - Hadikusumah, Rizkitaami Azqi; Nurmasari, Nuraini Desty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of financial literacy and financial behavior on the financial well-being of students who received scholarships from the Indonesian International Student Mobility Awards (IISMA) in 2023. Design/methodology/approach – This quantitative study uses primary data collected through questionnaires distributed to IISMA scholarship recipients. From a population of 150 students, respondents were selected using simple random sampling. The research instruments were tested for validity and reliability, followed by classical assumption testing and data analysis. Findings – The results indicate that financial literacy has a significant positive influence on financial well-being, suggesting that higher financial knowledge contributes to better financial conditions. Financial behavior also has a significant positive influence on financial well-being, demonstrating that effective financial practices improve students’ financial outcomes. Originality/value – This study contributes to financial well-being literature by examining a unique population of Indonesian students participating in international mobility programs. The findings highlight the importance of integrating structured financial education into student mobility programs to strengthen financial resilience and long-term well-being.